Comparative Performance Evaluation of Ryu and OpenDaylight SDN Controllers Using Mininet - mahmoud, huda; Nuredin Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2026)
Software-Defined Networking (SDN) enables centralized control and programmability by decoupling the control plane from the data plane. Since the SDN controller directly influences network behavior, evaluating controller performance is essential for effective deployment. This paper presents an experimental comparison of two widely used open-source SDN controllers, Ryu and OpenDaylight (ODL), using the Mininet network emulator and OpenFlow 1.3. The evaluation is conducted under identical small-scale tree topologies. Key performance metrics, including latency, throughput, and packet loss, are measured using ICMP and TCP traffic. The experimental results show noticeable differences in controller behavior, particularly in latency and packet loss, while both controllers exhibit comparable throughput under low to moderate traffic conditions. The study demonstrates the suitability of Mininet for SDN performance evaluation and provides quantitative results that support informed controller selection in experimental environments.